Methane decomposition for hydrogen production over biomass fly ash-based CeO2 nanowires promoted cobalt catalyst. Issue 5 (October 2021) - Raza, Jehangeer; Khoja, Asif Hussain; Naqvi, Salman Raza; Mehran, Muhammad Taqi; Shakir, Sehar; Liaquat, Rabia; Tahir, Muhammad; Ali, Ghulam
Abstract: In this work, the biomass fly ash (BFA) was investigated as a potential catalyst for the thermo-catalytic decomposition of methane and attractive approach for hydrogen (H2 ) production. The BFA based CeO2 nanowires promoted cobalt catalyst was synthesized for catalytic methane (CH4 ) decomposition and was tested in a fixed bed reactor. The physicochemical properties of the catalyst were investigated using various techniques such as X-ray powder diffraction, scanning electron microscopy, energy-dispersive X-ray spectroscopy, thermal gravimetric analysis, and Fourier transformed infrared. The pure crystalline micro-flake BFA was modified using synthesized CeO2 nanowires and the resulted micro flakes cross-linked with nanowires shown thermal stability up to 900 °C. The high stability of the catalyst makes it suitable for the thermal catalytic decomposition of methane. The activity of the catalyst was tested at 850 °C to analyze the H2 production and CH4 conversion. The obtained results revealed that support and promoter exhibit a strong impact on the CH4 conversion and H2 yield in catalyst screening tests. A maximum conversion of 71% for CH4 with 44.9% H2 yield was recorded for 34 h on stream activity while using 5% Co/CeO2 -BFA as the catalyst. While BFA and Co-BFA as catalyst showed 36% and 47% conversion of CH4, respectively which indicates that the addition of promoter shows an increase in values of both conversion of CH4 and H2 yield. Compared to traditional catalyst support, the use of waste-sourced catalyst support for CH4 decomposition provides a greener and more economical route for H2 production. Graphical Abstract: ga1 Highlights: Co loaded CeO2 nanowire promoted biomass fly ash catalyst is synthesized. CeO2 nanowire loading enhanced the H2 production in methane decomposition. Stability over 34 h is reported with no reduction in activity.